2013
DOI: 10.1155/2013/424313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Facial Cosmetic Acupuncture on Facial Elasticity: An Open-Label, Single-Arm Pilot Study

Abstract: Background. The use of acupuncture for cosmetic purposes has gained popularity worldwide. Facial cosmetic acupuncture (FCA) is applied to the head, face, and neck. However, little evidence supports the efficacy and safety of FCA. We hypothesized that FCA affects facial elasticity by restoring resting mimetic muscle tone through the insertion of needles into the muscles of the head, face, and neck. Methods. This open-label, single-arm pilot study was implemented at Kyung Hee University Hospital at Gangdong from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 9 publications
0
18
0
3
Order By: Relevance
“…33 Finally, a study of 27 women found that acupuncture resulted in statistically significant changes in Moiré topography, suggestive of improvement in facial elasticity. 35 …”
Section: Resultsmentioning
confidence: 99%
“…33 Finally, a study of 27 women found that acupuncture resulted in statistically significant changes in Moiré topography, suggestive of improvement in facial elasticity. 35 …”
Section: Resultsmentioning
confidence: 99%
“…Both authors cross-checked eligible studies; any disagreements regarding the extraction of study data were resolved www.jcosmetmed.org by discussion to reach consensus. We extracted the following data from the articles selected for inclusion: authors, year of publication, types of cosmetic condition, study design, sample size, interventions, controls, duration of treatment, outcome measures, safety reports, and the main findings (Table 1) [8][9][10][11][12][13][14]. We also extracted data regarding statistical procedures, ethics, and adherence to the Standards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA) ( Table 2) [8][9][10][11][12][13][14][15].…”
Section: Data Extractionmentioning
confidence: 99%
“…1, in accordance with PRISMA guidelines [7]. Finally, a total of 2 RCTs [8,14] and 5 prospective, experimental studies [9][10][11][12][13] (Chinese, n=2; English, n=2; Korean, n=3) were included in our review. Detailed characteristics of the 7 studies included are summarized in Table 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations